[Ag71(S-tBu)31(Dppm)](SbF6)2: an intermediate-sized metalloid silver nanocluster containing a building block of Ag64. Issue 80 (20th September 2021) - Zhou, Manman; Bao, Yizheng; Jin, Shan; Wen, Shuaishuai; Chen, Shuang; Zhu, Manzhou
Abstract : An intermediate-sized metalloid silver nanocluster [Ag71 (S- t Bu)31 (Dppm)](SbF6 )2 was reported, whose Ag23 unit provides a deeper understanding on Marks truncation, and Ag64 could serve as an assemble block to predict structures of larger nanoclusters. Abstract : An intermediate-sized atomically precise metalloid silver nanocluster [Ag71 (SR)31 (Dppm)](SbF6 )2 (Dppm = bis (diphenylphosphino)methane, SR = S- t Bu) is reported, which comprises one building block Ag64, six SR5 pentagons, one sole SR ligand, a DppmAg2 handle, and an Ag5 lid. Structurally, a decahedron Ag23 kernel is observed in the metalloid silver nanocluster. Moreover, the Ag64 unit provides insights into the growth of large clusters such as Ag136 (SR)64 Cl3 and Ag141 (SR)40 Br12 via assembly. The observed decahedron Ag23 provides a deeper understanding on Marks decahedron in larger nanoclusters, and the [Ag71 (S- t Bu)31 (Dppm)](SbF6 )2 uses Ag64 as a building block to predict the structure of larger metalloid nanoclusters.